Glutamate Cysteine Ligase—Modulatory Subunit Knockout Mouse Shows Normal Insulin Sensitivity but Reduced Liver Glycogen Storage - Lavoie, Suzie; Steullet, Pascal; Kulak, Anita; Preitner, Frederic; Do, Kim Q.; Magistretti, Pierre J. (Frontiers in Physiology, 2016)
Glutathione (GSH) deficits have been observed in several mental or degenerative illness, and so has the metabolic syndrome. The impact of a decreased glucose metabolism on the GSH system is well known, but the effect of decreased GSH levels on the energy metabolism is unclear. The aim of the present study was to investigate the sensitivity to insulin in the mouse knockout (KO) for the modulatory subunit of the glutamate cysteine ligase (GCLM), the rate-limiting enzyme of GSH synthesis. Compared to wildtype (WT) mice, GCLM-KO mice presented with reduced basal plasma glucose and insulin levels. During an insulin tolerance test, GCLM-KO mice showed a normal fall in glycemia, indicating normal insulin secretion. However, during the recovery phase, plasma glucose levels remained lower for longer in KO mice despite normal plasma glucagon levels. This is consistent with a normal counterregulatory hormonal response but impaired mobilization of glucose from endogenous stores. Following a resident-intruder stress, during which stress hormones mobilize glucose from hepatic glycogen stores, KO mice showed a lower hyperglycemic level despite higher plasma cortisol levels when compared to WT mice. The lower hepatic glycogen levels observed in GCLM-KO mice could explain the impaired glycogen mobilisation following induced hypoglycemia. Altogether, our results indicate that reduced liver glycogen availability, as observed in GCLM-KO mice, could be at the origin of their lower basal and challenged glycemia. Further studies will be necessary to understand how a GSH deficit, typically observed in GCLM-KO mice, leads to a deficit in liver glycogen storage.